Nutrient intake and digestibility of various winter fodders fed to Beetal goats and Lohi sheep - Nasrullah; M. Abdullah; K. Javed; J. A. Bhatti; A. N. Khosa; I. B. Marghazani; J. Sales; M. Fiaz; N. Ahmad (Journal of Animal and Plant Sciences, 2015)
Nutrient intake and digestibility of berseem clover (Trifolium alexandrium), lucerne (Medicago Sativa) and oats (Avena sativa) as winter fodders were fed to female goats (n = 45, age = 720 days, body weight = 32 kg) and sheep (n = 45, age = 690 days, body weight = 32 kg).  Intakes of dry matter (DM), crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), and gross energy (GE) were determined over a 30-day period.  In addition, total tract apparent digestibility of DM, CP, NDF and ADF were measured for 5 days with 3 animals per treatment.  Intakes of NDF and GE were higher (P<0.05) with lucerne compared to berseem clover independent of animal species, and oats presented the lowest (P<0.05) CP intake compared to other fodders.  The highest (P<0.05) CP digestibility was obtained with feeding of lucerne, with NDF digestibility comparable among fodders within animal species.  With the exception of DM, intakes and digestibilities of nutrients were higher (P<0.05) in goats than in sheep.
Keywords: Goats; sheep; winter fodders; nutrient intake; digestibility